Physiology - Preston, Robin R.; Wilson, Thad E (Lippincott's illustrated reviews., 2013)
Brings physiology clearly into focus. Brand new to the LIR arsenal, this title tells the story of who we are, how we live, and, ultimately, how we die. It identifies organ function and then shows how cells and tissues are designed to fulfill that function.